2016
DOI: 10.1016/j.jmb.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The Structure-Specific Recognition Protein 1 Associates with Lens Epithelium-Derived Growth Factor Proteins and Modulates HIV-1 Replication

Abstract: The lens epithelium-derived growth factor p75 (LEDGF/p75) is a chromatin-bound protein essential for efficient lentiviral integration. Genome-wide studies have located LEDGF/p75 inside actively transcribed genes where it mediates lentiviral integration. Although its role in HIV-1 integration is clearly established, the role of LEDGF/p75-associated proteins in HIV-1 infection remains unexplored. Using protein-protein interaction assays, we demonstrated that LEDGF/p75 complexes with a chromatin remodeling comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 73 publications
(142 reference statements)
0
17
0
Order By: Relevance
“…As shown in Fig. 1 b, no interaction was detected between IN/IBD/FACT by co-immunoprecipitation suggesting that the formation of the IN/LEDGF/FACT complex requires the previously reported physical association between FACT and LEDGF/p75 mediated by SSRP1 and PWWP domains [ 21 ].…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…As shown in Fig. 1 b, no interaction was detected between IN/IBD/FACT by co-immunoprecipitation suggesting that the formation of the IN/LEDGF/FACT complex requires the previously reported physical association between FACT and LEDGF/p75 mediated by SSRP1 and PWWP domains [ 21 ].…”
Section: Resultsmentioning
confidence: 73%
“…1 a). The close proximity found between SSRP1 and LEDGF/p75 protein in cells strongly supports the enrichment of FACT in the chromatin regions targeted by HIV-1 integration complexes [ 21 ]. Consequently, in view of (i) the histone chaperone activity of FACT, (ii) the previously reported links between this complex and HIV-1 replication and (iii) the importance of chromatin remodeling in regulating HIV-1 integration we further analyzed its potential function in modulating the insertion of viral DNA into chromatin.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Subsequent studies revealed that DFS70/ LEDGF critically associates with the MLL/Menin transcription complex to drive the expression of Hox genes and oncogenic transformation in leukemias caused by the MLL gene [75]. More recently, El Ashkar et al [76] PWWP [156] demonstrated that conditional knockout of the Psip1 gene (which encodes DFS70/LEDGF) from blood cells in a mouse model was dispensable for normal hematopoiesis but critical for MLL-mediated leukemogenesis. Consistent with this, leukemia cells expressing MLL and overexpressing DFS70/LEDGF IBD mutants were defective for MLL interactions and displayed decreased clonogenic growth [77].…”
Section: Oncoprotein Functionsmentioning
confidence: 99%